Global recognition of the importance of nature-based solutions to the impacts of climate change. (2020) - Seddon, Nathalie; Daniels, Elizabeth; Davis, Rowan; Chausson, Alexandre; Harris, Rian; Hou-Jones, Xiaoting; Huq, Saleemul; Kapos, Valerie; Mace, Georgina M.; Rizvi, Ali Raza; Reid, Hannah; Roe, Dilys; et al.
Non-technical summary: Ecosystems across the globe are vulnerable to the effects of climate change, as are the communities that depend on them. However, ecosystems can also protect people from climate change impacts. As the evidence base strengthens, nature-based solutions (NbS) are increasingly prominent in climate change policy, especially in developing nations. Yet intentions rarely translate into measurable, evidence-based targets. As Paris Agreement signatories revise their Nationally Determined Contributions, we argue that NbS are key to meeting global goals for climate and biodiversity, and we urge researchers to work more closely with policy-makers to identify targets that benefit both people and ecosystems. Technical summary: Recent research demonstrates that nature-based solutions (NbS) can help protect communities and infrastructure from the impacts of climate change while providing a range of other benefits for society. As nations revise or prepare new Nationally Determined Contributions (NDCs) in support of the Paris Agreement, there is a major opportunity to increase global ambition on NbS. To support this process and to provide a baseline against which ambition for NbS can be tracked, here we report on the prominence of NbS in the 168 NDCs that were submitted to the United Nations Framework Convention on Climate Change. In total, 104 nations include NbS in the adaptation component of their NDCs, 77 nations include them in both their adaptation and mitigation components and an additional 27 include them as part of their mitigation plans only. In other words, 131 nations – or 66% of all signatories to the Paris Agreement – have articulated intentions of working with ecosystems, in one form or another. However, national intentions to deliver NbS for adaptation vary by level of economic development, region and habitat type, and rarely translate into measurable evidence-based targets. We discuss possible reasons for these findings and provide recommendations on how national governments, practitioners and researchers can together enhance ambition for NbS to climate change impacts. As climate pledges are revised during successive global 'stock takes' of the Paris Agreement, we urge the research community to work closely with practitioners and policy-makers to identify meaningful targets that benefit both people and the ecosystems on which they depend.